Down regulation of glutathione and glutamate cysteine ligase in the inflammatory response of macrophages - Zhang, Hongqiao (Free Radic Biol Med, 2020)
Glutathione (GSH) plays critical roles in the inflammatory response by acting as the master substrate for antioxidant enzymes and an important anti-inflammatory agent. In the early phase of the inflammatory response of macrophages, GSH content is decreased due to the down regulation of the catalytic subunit of glutamate cysteine ligase (GCLC). In the current study we investigated the underlying mechanism for this phenomenon. In human THP1-differentiated macrophages, GCLC mRNA had a half-life of 4 h under basal conditions, and it was significantly reduced to less than 2 h upon exposure to lipopolysaccharide (LPS), suggesting an increased decay of GCLC mRNA in the inflammatory response. The half-life of GCLC protein was >10 h under basal conditions, and upon LPS exposure the degradation rate of GCLC protein was significantly increased. The pan-caspase inhibitor Z-VAD-FMK but not the proteasome inhibitor MG132, prevented the down regulation of GCLC protein caused by LPS. Both caspase inhibitor Z-LEVD-FMK and siRNA of caspase-5 abrogated LPS-induced degradation of GCLC protein. In addition, supplement with γ-GC, the GCLC product, efficiently restored GSH content and suppressed the induction of NF-κB activity by LPS. In conclusion, these data suggest that GCLC down-regulation in the inflammatory response of macrophages is mediated through both increased mRNA decay and caspase-5-mediated GCLC protein degradation, and γ-GC is an efficient agent to restore GSH and regulate the inflammatory response.